From Domestic Devotion to the Church Altar: Venerating Icons in the Late Medieval and Early Modern Adriatic - Voulgaropoulou, Margarita (Religions, 2019)
Although traditionally associated with Eastern Christianity, the practice of venerating icons became deeply rooted in the Catholic societies of the broad Adriatic region from the Late Middle Ages onwards and was an indispensable part of everyday popular piety. The evidence lies in the massive amount of icons located today in public and private collections throughout the Italian Peninsula, Croatia, Slovenia, and Montenegro. At a time when Greeks were branded as "schismatics", and although the Byzantine maniera greca had become obsolete in Western European art, icon painting managed to survive at the margins of the Renaissance, and ultimately went through its own renaissance in the sixteenth century. Omnipresent in Catholic households, icons were very often donated to churches as votive offerings and were gradually transformed into the focal points of collective public devotion. Through the combined study of visual evidence, archival records and literary sources, this article will shed light on the socio-political, confessional, and artistic dynamics that allowed for Byzantine or Byzantinizing icons to gain unprecedented popularity throughout the Catholic milieus of the Late Medieval and Early Modern Adriatic, and become integrated into domestic and public devotional practices.